Evaluasi Pemborosoan Mesin Bending Berbasis Pendekatan Statistical Process Control dan Overall Equipment Effectivenes - Ahmad Syahri Muzakki; Yanuar Pandu Negoro; Hidayat Hidayat (G-Tech: Jurnal Teknologi Terapan, 2024)
PT. ASM is a company operating in the steel sector. In production, it is of course important to maintain machine productivity to maintain production quality performance. In the research, problems were found in the form of machine damage which resulted in production stopping. In this research, the Statistical Quality Control (SQC) method is applied as a quality management approach to control process and product quality by integrating Overall Equipment Effectiveness (OEE) and SQC. In research, there are two types of data, namely primary data and secondary data which are used as references to facilitate the problem solving process. Primary data was obtained through interviews related to the production process, machine function, and causes of defects in production, while secondary data was obtained from company data recaps related to defects in production. Based on the results of the Pareto diagram, it was found that 55% of the problems were imprecise, while 45% were caused by iron cracking during the production process. Thus, it can be concluded that product defects are mainly caused by cracks in the iron and lack of precision in the machine